PEMANFAATAN APLIKASI CANVA (CODING WARNA) DALAM PEMBUATAN MEDIA PEMBELAJARAN DI SDIT MARYAM MURAITH OKU TIMUR : PEMANFAATAN APLIKASI CANVA (CODING WARNA) DALAM PEMBUATAN MEDIA PEMBELAJARAN DI SDIT MARYAM MURAITH OKU TIMUR - Qurnia Permata sari; Muhammad Amin Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and evaluation of using the Canva application with a color-coding method in developing learning media at SD IT Maryam Muraith. The subjects of this research were first-grade students at SD IT Maryam Muraith during the even semester of the 2025/2026 academic year. The focus of this study is the utilization of information and communication technology to help elementary school children learn and recognize the vowel letters A, I, U, E, and O in a fun way that matches their learning styles. Data were obtained from the stages of planning, implementation, and evaluation of the learning process. The results of this study can serve as a reference for teachers and the general public in utilizing Canva with a color-coding method. The colorful ship-themed media created using Canva increased student engagement, learning enthusiasm, and supported teachers in explaining vowel letters. The evaluation results show that most students have developed very well and in accordance with learning expectations. This study provides a new innovation in creating learning media for elementary school students. The difference from previous studies lies in its focus on helping children learn vowel letters in an enjoyable way and supporting visual learning styles.